해양 규조류 Cyclotella meneghiniana의 성장단계에 따른 비타민(B 1 , B 7 , B 12 ) 및 특이적 미생물의 변동 - 최원지; 기장서; Choi, Won-Ji; Ki, Jang-Seu (Ocean and polar research, 2019)
Diatom growth is affected by associated bacteria that probably provide useful substances like vitamins. In the present study, we analysed the variation of vitamins $B_1$, $B_7$ and $B_{12}$ on the growth stages of the marine diatom Cyclotella meneghiniana and assessed putative vitamin-producing bacteria (e.g., ${α}$- and ${γ}$-proteobacteria). HPLC analysis showed that total amounts of vitamins $B_1$ and $B_{12}$ decreased with cell growth, whereas vitamin $B_7$ increased gradually on the growth stages. $B_1$ and $B_{12}$ measured 0.5% and 0.18% at the stationary phase, following 0.25% and 0.72% at the lag phase. They considerably increased to 0.75% and 0.77% at the death stage. 16S pyrosequencing showed relatively high ratios of ${α}$- and ${γ}$-proteobacteria in all the growth stages of the C. meneghiniana. In addition, we detected previously-reported vitamin-producing bacteria, such as Marinobacter, in high numbers. The species was dorminant in the lag (relative abundance 72%) and exponetial (72%) stages, whareas it decreased in the stationary (49%) and death (48%) stages. These results suggest that vitamins $B_1$ or $B_{12}$ may be necesaary for diatom growth and that associated bacteria, including Marinobacter, may produce these substances for the cell growth of C. meneghiniana.